2012
DOI: 10.1007/s10695-012-9725-y
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone attenuates stress-induced suppression of LH secretion in the pituitary gland in the Cichlid fish Oreochromis mossambicus: evidence for the opioidergic mediation of reproductive stress response

Abstract: Opioid peptide β-endorphin (β-EP) plays a modulatory role in vertebrate reproduction. However, the role of opioid peptides in reproductive stress response is least understood in fishes. The aim of the present study was to determine the effect of different doses of β-EP on luteinizing hormone (LH) secretion in normal and the opioid receptor antagonist naltrexone (NALT) in stressed female tilapia Oreochromis mossambicus. Administration of 4 μg β-EP, but not 0.5 or 1.5 μg β-EP, daily for 22 days caused suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Complete blockade of the immunoreactions following these control procedures confirmed the specificity of the antisera. The specificity of LHβ antiserum used in the present study has also been reported previously for O. mossambicus (Chabbi and Ganesh, ; Ganesh and Chabbi, ), C. mrigala (Sakharkar et al, ), and Clarius batrachus (Mazumdar et al, ; Barsagade et al, ; Singh et al, ).…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Complete blockade of the immunoreactions following these control procedures confirmed the specificity of the antisera. The specificity of LHβ antiserum used in the present study has also been reported previously for O. mossambicus (Chabbi and Ganesh, ; Ganesh and Chabbi, ), C. mrigala (Sakharkar et al, ), and Clarius batrachus (Mazumdar et al, ; Barsagade et al, ; Singh et al, ).…”
Section: Methodssupporting
confidence: 86%
“…For instance, opioid peptide β‐endorphin is released in response to stress in the fish gilthead sea bream Sparus aurata (Mosconi et al, ; Arends et al, ). Our previous studies also have suggested a role for the involvement of β‐endorphin in mediation of reproductive stress response as shown by the suppression of LH secretion in the pituitary gland (Ganesh and Chabbi, ) and inhibition of vitellogenic follicular growth (Chabbi and Ganesh, ) in O. mossambicus . Therefore, the possibility of involvement of other inhibitory factors, which might act at the multiple sites of endocrine axis during reproductive stress response, cannot be ruled out for this species.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…β-endorphin increases energy intake and body weight [ 59 ], at least partially via antagonism of the anorexigenic and weight-reducing effect of α-MSH [ 60 ]. β-endorphin is also known to inhibit the hypothalamo-pituitary-gonadal axis in several species, via actions in the hypothalamus and peripheral tissues [ 61 , 62 ], consistent with the significantly reduced seminal vesicle weight seen in mice on the continuous but not the intermittent diet. These suppositions are speculative, however, and further work would be required to show whether or not reduced hypothalamic POMC expression—as well as other pathways, such as reduced gut nutrient absorption, increased thyroid function and increased energy expenditure—might be related to the effects of intermittent versus continuous energy restriction.…”
Section: Discussionmentioning
confidence: 86%
“…Endogenous opioid peptides have been shown to be involved in the regulation of several physiological functions, including reproduction, in different vertebrates (Ciarcia et al ., ; Facchinetti et al ., ; Faletti et al ., ; Ganesh & Yajurvedi, ; Leadem & Kalra, ; Olson et al ., ; Polzonetti‐Magni et al ., ; Zerani & Gobbetti, ). Among fishes, treatment with an opioid peptide, β‐endorphin (β‐EP), inhibits the function of the pituitary–ovary axis (Chabbi & Ganesh, ; Ganesh & Chabbi, ), whereas a dose‐dependent stimulatory as well as an inhibitory effect of leucine enkephalin on reproductive axis is demonstrated in the cichlid fish Oreochromis mossambicus (Peters 1852) (Vijayalaxmi & Ganesh, ). Dynorphin is another class of opioid peptide, which is produced from the prodynorphin gene and exists in different forms such as dynorphin‐A (DYN), dynorphin‐B and β‐neoendorphin, among which dynorphin‐A (1–17) is highly conserved and most potent (Civelli et al ., ; James et al ., ).…”
Section: Introductionmentioning
confidence: 99%